2023
DOI: 10.20944/preprints202301.0132.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proposal of a Maturity Model for Supply Chain Sustainability

Abstract: Nowadays, frameworks and models are critical to enabling organizations to identify their current sustainability integration into business and to follow up on these initiatives over time. In this context, the maturity models offer a structured way of analyzing how a supply chain meets specific sustainability requirements and which areas demand attention to reach maturity levels. This study proposes a five-level maturity model to help supply chains identify their level of engagement with sustainability practices… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…These areas are also considered essential components to assess the evolution in terms of sustainability, addressing an intracompany perspective and the SC perspective (Correia et al, 2018). Based on a systematic literature review of supply chain maturity models with sustainability concerns, Correia et al (2017) identified several critical success factors for implementing a sustainable SC that coincide with some of these areas.…”
Section: Sustainability Supply Chain Practicesmentioning
confidence: 99%
“…These areas are also considered essential components to assess the evolution in terms of sustainability, addressing an intracompany perspective and the SC perspective (Correia et al, 2018). Based on a systematic literature review of supply chain maturity models with sustainability concerns, Correia et al (2017) identified several critical success factors for implementing a sustainable SC that coincide with some of these areas.…”
Section: Sustainability Supply Chain Practicesmentioning
confidence: 99%